The agency of the Holy Spirit and heuristic categories for discernment in spirituality - Venter, Rian (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Living in a complex world with many challenges may render discernment as Christian spiritual practice increasingly important. If discernment is understood as an interpretation of the movement of the Holy Spirit in life, one obvious and fruitful avenue to gain better insight into this may entail an exploration of the very nature of this agency. To map the work of the Spirit is a striking hiatus in scholarly literature on discernment, and the article intends to address this. The need is for heuristic, that is, problem-solving, categories for reflecting on the agency of the Spirit. This article specifically contributes towards exploring such insight by studying contemporary developments in pneumatology. In recent study on the work of the Spirit, seven trends are investigated, and corresponding notions such as novelty, emergence, justice, hospitality, beauty, the impossible, and relationality emerge as ways to interpret the movement of the Spirit. These motifs, it is argued, may provide a lens to discover the divine possibilities in each moment in life and to understand discernment better.